Fahrenheit 9/11 - Moore, Michael, 1954 Apr. 23-; Baker, James Addison, 1930-; Gore, Albert, 1948-; Daschle, Thomas; Bush, George W. (George Walker), 1946-; Rice, Condoleezza, 1954-; Lion's Gate Films (Los Angeles, Calif.); IFC Films; Fellowship Adventure Group; Dog Eat Dog Films; Columbia TriStar Home Entertainment (Firm) (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
Through actual footage, interviews, and declassified documents, Michael Moore illustrates the connections President Bush has to the royal house of Saud of Saudia Arabia and the bin Laden's, how the president got elected on fraudulent circumstances and then proceeded to blunder through his duties while ignoring warnings of the looming betrayal by his foreign partners. When the treachery hits with the 9/11 attacks, Moore explains how Bush failed to take immediate action to defend the nation.
Anamorphic widescreen (1.78:1).
Special features: "The release of 'Fahrenheit 9/11'" featurette; Montage: the people of Iraq on the eve of invasion; New scene: Homeland Security, Miami style; Outside Abu Ghraib Prison; Eyewitness account from Samara, Iraq; Extended interview: More with Abdul Henderson; Lila Lipscomb at the Washington, D.C. premiere; Arab-American comediens--their acts and experiences after 9/11; Condoleezza Rice's 9/11 Commission Testimony; Rose Garden press briefing after 9/11 Commission appearance.
Camera, Mike Desjarlais ; editors, Kurt Engfehr, Christopher Seward, T. Woody Richman ; music, Jeff Gibbs.
Michael Moore, James Baker, Al Gore, Tom Daschle, George W. Bush, Condoleezza Rice, Byron Dorgan, Craig Unger, Jack Cloonan, James Moore, Dan Briody, Carol Ashley, Thomas H. Kean, Rosemary Dillard, Richard Clarke, Martha Brill Olcott, Jim McDermott, Porter Goss, John Conyers, Tammy Baldwin, Lila Lipscomb.
MPAA rating: R; for some violent and disturbing images, and for language.
DVD; Dolby digital 5.1.
Keywords: Bush, George W. (George Walker), 1946-; September 11 Terrorist Attacks, 2001.; Contested elections; Films for the hearing impaired; United States -- Politics and government -- 2001-2009; Documentary films